2002
DOI: 10.1023/a:1022966930861
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The relations between disturbance regime and landscape patterns have been developed from a theoretical perspective, but few studies have tested these relations when forces promoting opposing heterogeneity patterns are simultaneously operating on a landscape. This work provides quantitative evidence of these relations in areas dominated by human activity, showing that landscape heterogeneity decreases disturbance spread. In turn, disturbance introduces a source of landscape heterogeneity, but it is not enough t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(41 citation statements)
references
References 50 publications
2
33
0
2
Order By: Relevance
“…The ratio ␤ anthropogenic ͞␤ lightning Ͼ 1 in the eastern third of the conterminous U.S. suggests a potential influence of human activity on the relative scaling of wildfire-burned areas, because these areas are more populated. It has been suggested (20) that increased landscape heterogeneity decreases disturbance (e.g., wildfire) spread. Historic anthropogenic forest clearance, resulting in forests fragmented by agricultural and urban land cover, has increased the heterogeneity of eastern landscapes (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ratio ␤ anthropogenic ͞␤ lightning Ͼ 1 in the eastern third of the conterminous U.S. suggests a potential influence of human activity on the relative scaling of wildfire-burned areas, because these areas are more populated. It has been suggested (20) that increased landscape heterogeneity decreases disturbance (e.g., wildfire) spread. Historic anthropogenic forest clearance, resulting in forests fragmented by agricultural and urban land cover, has increased the heterogeneity of eastern landscapes (40).…”
Section: Discussionmentioning
confidence: 99%
“…With implications for hazard management, climate studies, and ecosystem research, there is, therefore, significant interest in appropriate analysis of historical wildfire databases. Insightful studies using wildfire database statistics exist (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) but are often hampered by the low spatial and͞or temporal resolution of their data sets. Here, we use a high-resolution database of wildfires for the conterminous United States (U.S.), combined with techniques drawn from recent advances in statistical physics and complexity theory, to examine U.S. wildfire statistics in a spatially and temporally explicit manner.…”
mentioning
confidence: 99%
“…This results in vegetation consisting of scrub (Mermoz et al 2005, Pardo & Gil 2005. Several authors found that the main causes of forest fires are socioeconomic in nature (Vázquez & Moreno 2001, Lloret et al 2002. MareyPérez & Rodríguez-Vicente (2008) included conflicts resulting from communal management and ownership as the main causes in this region.…”
Section: Groupmentioning
confidence: 99%
“…Similar climates are found in Spain, Portugal, Greece, France and Italy. Human influence has a high impact on initiation and spread of forest fires (Le Houérou, 1987;Leone et al, 2002;Lloret et al, 2002;Koutsias et al, 2005).…”
Section: Study Areamentioning
confidence: 99%